Modeling and simulation of Electromagnetic Fields on a Floating Aluminium - Narukullapati, Bharath Kumar; Bhattacharya, T K; Reddy, ANaveen; Gollapudi, Srikanth (International Journal of Engineering and Technology, 2018)
The electromagnetic field calculation for a floating aluminum disc is difficult to calculate since the equation involved does not produce a closed solution. The numerical, analytical, semi-analytical techniques that are already developed to find these magnetic fields have no proper mathematical formulation when the disc is disturbed from its coaxial position. The stabilization of disc is going to be effected when the disc moves away from its coaxial position due to a change in inductance between the disc and coils, due to change in magnetic flux linkage, etc. In this paper, a 2D FEM model is developed to determine the magnetic fields on a floatingaluminum disc when it is moved away from its coaxial position. The 3D FEM model developed is simulated in both COMSOL-Multiphysics and ANSYS-Electronics. The results obtained by simulation are compared, for accuracy, with the numerical solution developed earlier using Finite Difference method (FDM) and also discussed.